Women's empowerment, production choices, and crop diversity in Burkina Faso, India, Malawi, and Tanzania: A secondary analysis of cross-sectional data - Connors, Kaela; Jaacks, Lindsay M.; Awasthi, Ananya; Becker, Karoline; Kerr, Rachel Bezner; Fivian, Emily; Gelli, Aulo; Harris-Fry, Helen; Heckert, Jessica; Kadiyala, Suneetha; Martinez, Elena M.; Santoso, Marianne V.; et al. (Elsevier, 2023)
Background: Bolstering farm-level crop diversity is one strategy to strengthen food system resilience and achieve global food security. Women who live in rural areas play an essential role in food production; therefore, we aimed to assess the associations between women's empowerment and crop diversity. Methods: In this secondary analysis of cross-sectional data, we used data from four cluster-randomised controlled trials done in Burkina Faso, India, Malawi, and Tanzania. We assessed women's empowerment using indicators from the Women's Empowerment in Agriculture Index. Farm-level crop diversity measures were the number of food crops grown, number of food groups grown, and if nutrient-dense crops were grown. We used a two-stage modelling approach. First, we analysed covariate-adjusted country-specific associations between women's empowerment and crop diversity indicators using multivariable generalised linear models. Second, we pooled country-specific associations using random-effects models. Findings: The final analytic sample included 1735 women from Burkina Faso, 4450 women from India, 547 women from Malawi, and 574 women from Tanzania. Across all countries, compared with households in which women provided input into fewer productive decisions, households of women with greater input into productive decisions produced more food crops (mean difference 0·36 [95% CI 0·16–0·55]), a higher number of food groups (mean difference 0·16 [0·06–0·25]), and more nutrient-dense crops (percentage point difference 3 [95% CI 3–4]). Across all countries, each additional community group a woman actively participated in was associated with cultivating a higher number of food crops (mean difference 0·20 [0·04–0·35]) and a higher number of food groups (mean difference 0·11 [0·03–0·18]), but not more nutrient-dense crops. In pooled associations from Burkina Faso and India, asset ownership was associated with cultivating a higher number of food crops (mean difference 0·08 [0·04–0·12]) and a higher number of food groups (mean difference 0·05 [0·04–0·07]), but not more nutrient-dense crops. Interpretation: Greater women's empowerment was associated with higher farm-level crop diversity among low-income agricultural households, suggesting that it could help enhance efforts to strengthen food system resilience.